1991
DOI: 10.1037/0022-3514.60.2.218
|View full text |Cite
|
Sign up to set email alerts
|

Social stigma: The affective consequences of attributional ambiguity.

Abstract: Two experiments investigated the hypothesis that the stigmatized can protect their self-esteem by attributing negative feedback to prejudice. Fifty-nine women participated in the 1st experiment. Women who received negative feedback from a prejudiced evaluator attributed the feedback to his prejudice and reported less depressed affect than women who received negative feedback from a nonprejudiced evaluator. In the 2nd experiment, 38 Black and 45 White students received interpersonal feedback from a White evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
683
6
10

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 753 publications
(725 citation statements)
references
References 71 publications
26
683
6
10
Order By: Relevance
“…That is, if people frequently fail to realize that they have been the victims of discrimination, this increases the likelihood that the status quo will forever remain the status quo. From a theoretical perspective, the minimization of personal disadvantage also flies in the face of a large research literature that has emphasized that stigmatized members often protect the self by making attributions to discrimination, rather than minimizing or denying it (Allport, 1954;Crocker & Major, 1989;Crocker, Voelkl, Testa, & Major, 1991;Dion & Earn, 1975). According to this perspective, stigmatized group members are highly aware of the negative stereotypes others hold of their group and are likely to attribute negative feedback to discrimination whenever cues of prejudice and discrimination are present (Major, Quinton, & McCoy, 2002; see also Feldman Barrett & Swim, 1998).…”
Section: Why Does It Matter?mentioning
confidence: 99%
See 1 more Smart Citation
“…That is, if people frequently fail to realize that they have been the victims of discrimination, this increases the likelihood that the status quo will forever remain the status quo. From a theoretical perspective, the minimization of personal disadvantage also flies in the face of a large research literature that has emphasized that stigmatized members often protect the self by making attributions to discrimination, rather than minimizing or denying it (Allport, 1954;Crocker & Major, 1989;Crocker, Voelkl, Testa, & Major, 1991;Dion & Earn, 1975). According to this perspective, stigmatized group members are highly aware of the negative stereotypes others hold of their group and are likely to attribute negative feedback to discrimination whenever cues of prejudice and discrimination are present (Major, Quinton, & McCoy, 2002; see also Feldman Barrett & Swim, 1998).…”
Section: Why Does It Matter?mentioning
confidence: 99%
“…To test the hypothesis that the need to belong influences judgments of the causes of personal discrimination in attributionally ambiguous situations, we conducted a conceptual replication of a study by Crocker et al (1991, Experiment 1). Crocker et al showed that women were more likely to attribute negative feedback to discrimination if the feedback came from a seemingly prejudiced as opposed to nonprejudiced (male) evaluator.…”
Section: Studymentioning
confidence: 99%
“…Further, Dardenne, Dumont, and Bollier (2007) found that "benevolent sexism" (i.e., the portrayal of women as warm but incompetent) led victims to experience self-doubt, whereas hostile sexism was more likely to result in victims' discounting of the opinions of harassers as discriminatory. Separately, Crocker, Voelkl, Testa, and Major (1991) found that participants who received negative feedback from a male evaluator, and who were in the experimental condition that enabled them to make an attribution of prejudice, reported a more positive mood than individuals who could not make an attribution of prejudice. Therefore, to the extent that victims are able to perceive sexual harassment as gender related, they may attribute the mistreatment to the perpetrator's prejudice toward their gender.…”
Section: Social Identity and Self-categorization Theories: Attacking mentioning
confidence: 99%
“…If anything, the available literature suggests that disidentification is more apt to be used as a coping mechanism at the level of the individual self (e.g., Gaertner et al, 1999, Experiment 1). Mussweiler, Gabriel, and Bodenhausen (2000) and Crocker, Voelki, Testa, and Major (1991) demonstrated that disidentification is used as a protective strategy in the face of threat to the individual self. Likewise, the tendency to publicly associate with a winning in-group is significantly more likely, if not done exclusively, following a threat to the individual self (Cialdini et al, 1976, Experiment 2).…”
Section: Alternative Explanationsmentioning
confidence: 99%